Political and Legal Policies in Determining Hijri Calendar among MABIMS Member Countries - Ahmad Wahidi; Mochammad Agus Rachmatulloh; Muhammad Syazwan Faid; Musataklima Musataklima (De Jure: Jurnal Hukum dan Syari'ah, 2026)
The determination of the beginning of Islamic months constitutes a crucial intersection between religious law, astronomical science, and state authority. In MABIMS Member Countries, variations in political configurations and state-religion relations have produced distinct legal policies governing the Islamic calendar, particularly regarding Ramadan, Shawwal, and Dhu al-Hijjah. This study aims to examine how legal politics shape state authority in determining the beginning of Islamic months and to analyse the legal consequences of these policies for legal certainty and public compliance among Muslim communities. This research employs a normative juridical method with conceptual and comparative approaches. Data were derived from an analysis of statutory regulations, official fatwas, state religious authority decisions, and regional coordination documents within the MABIMS framework, supported by scholarly perspectives in Islamic law, astronomy (ʿilm al-falak), and legal politics. The findings demonstrate that the determination of Islamic months is not primarily driven by the methodological choice between hisab (astronomical calculation) and rukyah (hilal observation), but rather by the political configuration and the degree of centralisation of state religious authority. Indonesia and Singapore, characterised by more pluralistic and participatory political systems, position the state as a coordinator and final legitimising authority while allowing limited pluralism in societal practice. In contrast, Malaysia and Brunei Darussalam adopt a highly centralised model of state religious authority, where the determination of Islamic months is a binding legal decision enforced through statutory sanctions. This study concludes that stronger state authority in religious governance correlates with higher levels of legal unification and compliance in the Islamic calendrical system. Accordingly, legal politics plays a decisive role in shaping the legal outcomes of determining the Islamic month in Southeast Asia, extending beyond doctrinal or jurisprudential debates alone. Keywords: beginning of the month; hisab rukyah; legal politics; MABIMS.